Digitization of Archives at Café Ganesha Mocktail Bandung - Rizky Zainab, Ellenia Rahmani; Sobandi, Ade; Rasto, Rasto (IJBLE Scientific Publications Community Inc., 2023)
This research aims to develop a digital filing system at the Ganesha Mocktail café in Bandung, West Java. This is intended to improve the existing archive storage system at the Ganesha Mocktail café so that the documents that are owned are stored properly. This type of research and development uses a Research and Development (RnD) design developed using the SDLC (System Development Life Cycle) model. The research stages start from system planning, system analysis, system design/development, to system implementation. This research produces a digital archive information system application for Café Ganesha Mocktail based on Microsoft Office Access. Through this application, Café Ganesha Mocktail can store files safely and easily find the documents needed.